Pakistan’s Struggle for Regional Economic Dominance: Analyzing Failures and Proposing Essential Policy Interventions - Umair, Muhammad (Journal of Public Policy Practitioners, 2023)
This policy paper is an inquisitive effort from a vantage point which aims to explore Pakistan’s economic prospects and identifies the key systemic issue of governance that has hampered Pakistan’s potential for regional economic dominance and requires intervention on priority. This paper underscores the critical role of system theory in policymaking, particularly when paralysis ensues due to intricate issues within the public sector. It advocates for a strategic approach by identifying key intervention areas and emphasizes the importance of adhering to broader governance principles within one’s sphere of influence. Additionally, it subtly touches upon the impact of foreign aid and political instability on economic growth. Through survey, statistics and literature review, this research narrows down the interventions necessary to navigate the challenging public policy regime in order to meet the objective of regional economic prosperity. It inspires the policymakers to contribute through the economic prism in their own area of influence for sustainable economic growth, instead of being trapped into inculpation.